2019
DOI: 10.3390/medicina55100648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Balance Taping Using Kinesiology Tape and Cross Taping on Shoulder Impingement Syndrome: A Case Report

Abstract: Background and objectives: Shoulder impingement syndrome (SIS) is the most common disorder among people with shoulder pain. The purpose of this case report was to investigate the effect of the combined application of balance taping using kinesiology tape and cross taping on a part-time worker with SIS. Case Report: Combined balance taping and cross taping was applied for 3 weeks (average, 16 hours per day) on a part-time worker with severe pain and a limited range of motion (ROM) in the shoulder who had visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The AET method consists of four steps [ 24 , 25 ]. First, for the posterior talar glide to increase ankle dorsiflexion, the ankle was slightly dorsiflexed and the tape was applied from the talus to the calcaneus on both sides ( Figure 2 B).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The AET method consists of four steps [ 24 , 25 ]. First, for the posterior talar glide to increase ankle dorsiflexion, the ankle was slightly dorsiflexed and the tape was applied from the talus to the calcaneus on both sides ( Figure 2 B).…”
Section: Case Reportmentioning
confidence: 99%
“…Finally, to strengthen the posterior talar glide and increase ankle dorsiflexion, while the ankles were held in a slight dorsiflexion state, the tape was applied over that from the first step ( Figure 2 E). To prevent skin irritation, the start and end points of the I-shaped elastic tape (approximately 2 cm) were applied without stretching [ 24 , 26 ], and the applied AET was removed within 24 h and reapplied daily, even if the subject did not experience itching [ 24 , 26 ].…”
Section: Case Reportmentioning
confidence: 99%
“…The cross tape is applied to an acupuncture or muscle tone point in the treatment of various musculoskeletal disorders or general medical conditions [1,2]. In previous studies, cross taping was shown to reduce pre-menstrual pain [3], increase proprioception and balance in the neck and ankle areas [4], and reduce pain and promote functional improvement in the treatment of shoulder impingement syndrome, where cross tape was combined with kinesiology tape and applied to the levator scapulae muscle [5].…”
mentioning
confidence: 99%